Pemodelan Pemilihan Moda Transportasi (Studi Kasus: Fakultas Ekonomi dan Bisnis Universitas Negeri Malang) - Rahardjo, Boedi; Yulianti, Monica; Pranoto, Pranoto (MEDIA KOMUNIKASI TEKNIK SIPIL, 2023)
A traveler will consider many things in choosing a mode because the availability of transportation modes is variated. The traveler's characteristics, the trip's characteristics, and the facilities of transportation mode characteristics can influence a person's decision in choosing a mode. The study of the selection of modes of transportation to campus by students, lecturers, and other workers at the Faculty of Economics and Business, State University of Malang, aims to describe the characteristics of mode users and determine the mode selection models to go to campus. This study used a descriptive analysis method to determine the characteristics of mode users and the binomial difference logit method for modeling transportation. The results of the study showed that five factors are most influential in choosing a mode between private transportation and public transportation at the Faculty of Economics and Business, the State University of Malang, namely ownership of a driving license, travel distance, the comfort of transportation, the safety of transportation, and availability of transportation which produces a regression model UKP – KU = -11.480 + 4.045 (X7) – 1.263 (X8) + 5.102 (X11) + 2.302 (X12) + 5.693 (X14). This model has an R2 value of 0.743 and a classification plot of 0.927. From the results of the modeling equation, the probability value of mode selection for private transportation is 0.997. In contrast, public transportation gets a probability value of 0.003.